2020
DOI: 10.1097/j.pain.0000000000001809
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapists' perceptions of learning and implementing a biopsychosocial intervention to treat musculoskeletal pain conditions: a systematic review and metasynthesis of qualitative studies

Abstract: Clinical practice guidelines recommend a biopsychosocial approach for the management of musculoskeletal pain conditions, but physiotherapists have reported feeling inadequately trained and lacking in confidence to deal with psychosocial issues. Although a growing number of studies are exploring physiotherapists' perceptions of biopsychosocial training, the results have not been synthesized. Therefore, the aim of this systematic review and metasynthesis of qualitative studies was to explore physiotherapists' pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 59 publications
7
83
0
2
Order By: Relevance
“…This requires complex changes in clinical routines, collaboration among disciplines, and changes in the organization of care, or even in cultural beliefs and attitudes [35]. However, in the review of Holopainen et al (2020), it was found that most biopsychosocial interventions to improve health care are focused on the individual skills of HCPs instead of on collaboration [36]. An added value of our study was the multidisciplinary transmural education days and practice meetings with all HCPs from primary, secondary, and tertiary care together, which also stimulated implementation at the group and organizational levels.…”
Section: Discussionmentioning
confidence: 99%
“…This requires complex changes in clinical routines, collaboration among disciplines, and changes in the organization of care, or even in cultural beliefs and attitudes [35]. However, in the review of Holopainen et al (2020), it was found that most biopsychosocial interventions to improve health care are focused on the individual skills of HCPs instead of on collaboration [36]. An added value of our study was the multidisciplinary transmural education days and practice meetings with all HCPs from primary, secondary, and tertiary care together, which also stimulated implementation at the group and organizational levels.…”
Section: Discussionmentioning
confidence: 99%
“…Alexanders [63] theorised that, as a consequence of a lack of training in psychology, physiotherapists might feel underprepared to assess and manage psychological factors. In a systematic review, Holpainen et al [64] identified that physiotherapists feel underprepared and uncomfortable dealing with psychosocial factors when implementing psychologically informed practice. Andrew et al [21] found that physiotherapists expressed little confidence in their ability to competently manage people with severe and persistent mental illness; largely due to a lack of training in mental health.…”
Section: My Wife Is a [Health Professional] So Occasionally [I Debrimentioning
confidence: 99%
“…Simulation of different situations might stimulate physiotherapist's confidence in handling new situations. Furthermore, booster sessions and providing feedback during the intervention (coaching on the job) may further improve cognitivebehavioural skills and confidence of physiotherapists [25,26].…”
Section: Summary Of Main Outcomesmentioning
confidence: 99%